Flutter behaviour of composite aircraft wings - Ashawesh, Gamal Mohamed (Cranfield University, 1999)
This research work presents series of investigations into the structural dynamics and dynamic aeroelastic (flutter) behaviour of composite and metal wings. The study begins with a literature review where the development and an over view of the previous investigations in this field are presented. Static stiffness is very important to any type of analysis, especially in both dynamic and flutter analysis as in this case. Therefore, different methods are presented and used for the determination of cross- sectional rigidities such as bending, torsional and bending-torsional coupling rigidities properties for beams constructed of laminated and thin-walled structures materials. A free vibration experimental analysis was conducted on the physical Cranfield Al aerobatic composite wing box structure. The composite wing box was exited in the frequency range of 0 to 300 Hz, with both sinusoidal and random excitations, which yields to six resonant frequencies. The theoretical free vibration and flutter analysis was then carried out firstly on the physical Cranfield Al aerobatic metal wing box. The metal wing was modeled using two techniques; the first model was a simplified wing structure (beam with lumped mass). This analysis of the simplified model was done using CALFUN program for the free vibration analysis and using MSC/NASTRAN for both free vibration and flutter analysis. The second model was a detailed model created by MSC/PATRAN and analyzed by MSC/NASTRAN for the free vibration and flutter analysis. The obtained results (natural frequencies and mode shapes) showed a good agreement between the simplified, detailed model and the experimental test. It was found that even with using the simplified model, but having the physical characteristics of the wing leads to a good agreement with the detailed model and experimental work. This also showed the importance of simplified model at early stage of the design to the structural designer in terms of the accuracy, time, and size of the model. Free vibration and flutter analysis was carried out on the Cranfield Al aerobatic composite wing box with the original laminate lay ups using Lanczos method for extracting the eigenvalues and eigenvectors and using PK method for finding the flutter speed and frequency provided by MSC/NASTRAN. The results were compared with the experimental vibration analysis and were found a large difference in the first frequency mode. To investigate the cause of the variation, a series of static loading tests were performed on the composite wing box. Also a comparison of the results between the metal and composite aerobatic wing box is presented. It was found that the large difference could be due to the combination of different parameters such as stiffness (age of the wing, delamination and boundary condition), and increase of mass of the physical wing box (due to environmental effect such as moisture) and modelling differences. The free vibration characteristics of ten wing models constructed from balanced and unbalanced laminate configurations were carried out using Lanczos method provided by MSC/NASTRAN. The analysis was done on ten wing models modeled to simulate Circumferentially Asymmetric Stiffness (CAS) and Circumferentially Uniform Stiffness (CUS). The static equivalent stiffness was calculated using two different modeling methods for a wide range of fibre angles 0 (- 90° to 90°) of the skins. The variations and the importance of the stiffness ratio (EI/GJ), parameter (K/GJ), and the frequency ratio (wb/(Ot) are illustrated against the fibre angle 0. It was found that the fundamental bending frequency is slightly lower in the case of CUS (K = 0) as compared to the CAS (K # 0), which was not the case in the plate model. Also, the first torsion frequency mode in the case of CUS was much lower than the first torsion frequency of the CAS, which was not the case of the plate model. However, the effect of bend-twist coupling stiffness on the mode shapes was pronounced in both structures especially at the area of higher coupling stiffness. The flutter analysis was done using the PK method for all the wing models of both (CAS) and (CUS) configurations. The results showed the optimum value of flutter speed and the importance of the stiffness ratio (EI/GJ), parameter (K/GJ), the frequency ratio (wb/wt), which will lead to the maximum flutter speed. The effects of the above parameters, geometrical coupling and the wash-in and washout on the non- dimensional flutter speed are presented. It was concluded that, negative bend-twist coupling stiffness is beneficial for flutter speed compared to the positive bend-twist coupling stiffness at 00<0<_30°. It was also found that the flutter speed for the CUS was higher at 00<0<_300 compared to the CAS. Also creating an offsite between the elastic axis and center of gravity (behind) decreases the flutter speed whereas having more ribs increases the flutter speed compared with adding stringers. The analysis was carried out on a more practical composite wing box, which was the physical Cranfield Al aerobatic composite wing box. There are some simplifications on the physical structure, which are the cancellation of the woven materials and keeping the same laminate lay ups for the upper and lower skin. The natural frequency and mode shapes was obtained and plotted against the fibre angle 0 of the upper and lower skin for the (CAS) and (CUS) configurations using both symmetric and asymmetric laminate for the upper and lower skin. The flutter analysis was done for the composite wing box for the same configurations as in the free vibration analysis. The effects of the fibre angle 0 of the upper and lower skin, material coupling stiffness, wash-in and wash-out, and structural damping on the non- dimensional flutter speed and flutter frequencies are illustrated. It was found that in this configurations both structural and bend-twist coupling are exist, negative bend- twist coupling (wash-in) increases the flutter speed compared with the positive bend- twist coupling, and the possibility of increasing the flutter speed at higher frequency ratio, structural coupling and positive bend-twist coupling (wash-out).